Left ventricular electrical potential measured by the NOGA XP electromechanical mapping method as a predictor of response to cardiac resynchronization therapy - Wilczek, Jacek; Jadczyk, Tomasz; Wojakowski, Wojciech; Gołba, Krzysztof S. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: The aim of the study was to determine whether left ventricular electrical potential measured by electromechanical mapping with the NOGA XP system has predictive value for response to CRT. Background: Approximately 30% of patients who undergo cardiac resynchronization therapy do not see the expected effects. Methods: The group of 38 patients qualified for CRT implantation were included in the study, of which 33 patients were analyzed. A 15% reduction in ESV after 6 months of pacing was used as a criterion for a positive response to CRT. The mean value and sum of unipolar and bipolar potentials obtained by mapping with the NOGA XP system and their predictive value in relation to the effect of CRT were analyzed using a bulls-eye projection at three levels: 1) the global value of the left ventricular (LV) potentials, 2) the potentials of the individual LV walls and 3) the mean value of the potentials of the individual segments (basal and middle) of the individual LV walls Results: 24 patients met the criterion of a positive response to CRT versus 9 non-responders. At the global analysis stage, the independent predictors of favorable response to CRT were the sum of the unipolar potential and bipolar mean potential. In the analysis of individual left ventricular walls, the mean bipolar potential of the anterior and posterior wall and in the unipolar system, mean septal potential were found to be an independent predictor of favorable response to CRT. In the detailed segmental analysis, the independent predictors were the bipolar potential of the mid-posterior wall segment and the basal anterior wall segment. Conclusions: Measurement of bipolar and unipolar electrical potentials with the NOGA XP system is a valuable method for predicting a favorable response to CRT.